2017
DOI: 10.1136/archdischild-2016-311449
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-minute consultation in the normal child: Challenges relating to sexuality and gender identity in children and young people

Abstract: Lesbian, gay, bisexual and transgender (LGBT+) young people face several challenges in their daily lives, including specific healthcare inequalities. Negative societal attitudes towards sexual and gender minorities, and the effects of regular experiences of bullying and homophobia/transphobia exacerbate the normal trials and tribulations of childhood and adolescence. Barriers to accessing healthy activities, such as sport, are created by perceived stigma and real-life experiences. Healthcare environments are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…One of the most commonly reported element of heteronormativity was a heterosexual assumption about SGM youth in healthcare (East and El Rayess, 1998;Scherzer, 2000;Ginsburg et al, 2002;Kitts, 2010;Arbeit et al, 2016;Fuzzell et al, 2016). This issue has been recognised in previous literature (O'Neill and Wakefield, 2017;Brooks et al, 2018), and its influences for SGM youth were identified in this review. One example of the influence of the heterosexual assumption in healthcare is lack of information that is relevant to SGM youth.…”
Section: Discussionmentioning
confidence: 84%
“…One of the most commonly reported element of heteronormativity was a heterosexual assumption about SGM youth in healthcare (East and El Rayess, 1998;Scherzer, 2000;Ginsburg et al, 2002;Kitts, 2010;Arbeit et al, 2016;Fuzzell et al, 2016). This issue has been recognised in previous literature (O'Neill and Wakefield, 2017;Brooks et al, 2018), and its influences for SGM youth were identified in this review. One example of the influence of the heterosexual assumption in healthcare is lack of information that is relevant to SGM youth.…”
Section: Discussionmentioning
confidence: 84%
“…Next, ask how the individual would like to be addressed in terms of name, title and pronoun. O’Neill and Wakefield’s 2016 article6 provides an excellent glossary for understanding gender and sexuality nomenclature but is summarised in box 2.…”
Section: Information Gatheringmentioning
confidence: 99%
“…"Transgender" continues to appear on patients' problem lists 4 . [48][49][50] Prejudice and discrimination against transgender people in biomedical research and medical practice are well established [1,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The misunderstanding and erasure of gender diversity has led to poor study design, additional barriers accessing care, unethical disclosure of 1 It is especially concerning that terms like "sodomy," "surgically transgendered transsexual," and "transvestic fetishism" persist in some terminologies.…”
Section: Introductionmentioning
confidence: 99%